New perspectives on distributive justice deep disagreements, pluralism, and the problem of consensus - Knoll, Manuel; Snyder, Stephen; Şimşek, Nurdane (De Gruyter, 2019)
Distributive justice is one of the most discussed topics in political philosophy. Focusing on the plurality of irreconcilable conceptions of social and political justice, this book presents an array of new perspectives on the topic. Bringing together more than 20 original essays of well-established and young international scholars, the volume is essential reading for anyone interested in social and political justice.